An Analysis of Students Reading Comprehension Difficulties - Wulandari, Riski; Azmi, Aulia; Aisyah, Noor; Azhimia, Faida (CV. Global Health Science Group, 2025)
Schools, as key educational institutions, play a vital role in fostering 21st-century skills, notably the 4Cs: critical thinking, creativity, communication, and collaboration. Among these, reading ability stands out as a fundamental skill in elementary education, essential for students' overall learning success. This study investigates the reading comprehension difficulties experienced by students at Sekolah Dasar Teologi Kristen Galilea Banjarmasin. The study aims to analyze these difficulties in depth to provide insights into improving reading instruction and enhancing student learning outcomes. Objective to determine the reading difficulties of grade five students at SDTK Galilea Banjarmasin. Quantitative descriptive method research design. The population is the grade five at SDTK Galilea Banjarmasin, with a total sample of fitteen students. This research was conducted by distributing questions to children. Based on the data it can be know that 53,32% students has difficulties in determining main idea, 36,66% of students has difficulties in understanding vocabulary, 29,99% of students has difficulties in finding detail information, 28,33% students has difficulties in locating references, 26,66% students has difficulties in making inferences. Based on the analysis of students’ reading comprehension test result at SDTK Galilea Banjarmasin it can be concluded that students face challenges in various aspects of reading comprehension. They particulary struggle with identifying main idea, identifying references, making references, locating detailed information in the text. These finding suggest that students’ overall reading comprehension is still low, indicating a need for targed instructional strategies to addres these issues in the learning procces.